Next Generation Information Technologies and Systems 6th International Conference, NGITS 2006, Kebbutz Sehfayim, Israel, July 4-6, 2006, Proceedings - Etzion, Opher; Kuflik, Tsvi; Motro, Amihai (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2006)
Information technology is a rapidly changing field in which researchers and developers must continuously set their vision on the next generation of technologies and the systems that they enable. Suitably, Next-Generation Information Technologies and Systems (NGITS) is an ongoing series of workshops that provides a forum for presenting and discussing the latest advances in information technology. NGITS took are international events held in Israel; previous workshops took place in 1993, 1995, 1997, 1999 and 2002. The call for papers for the 2006 workshop was answered by 138 papers on a very diverse range of subjects, thus presenting a considerable challenge to the Program Committee. Each of these papers received professional reviewing from at least three experts, and eventually 32 papers (less than 25%) were selected for presentation at the workshop and inclusion in these proceedings. Of these, 28 are full-length papers and 4 are short papers. In addition, several research works were selected to display "poster" presentations, and a number of research projects exhibited demonstrations. Finally, the workshop featured three keynote lectures by notable experts. The selected papers may be classified roughly in ten broad areas: ? Information systems development ? Distributed systems ? Semi-structured data ? Data mining and agent-oriented computing ? User-oriented design ? Frameworks, models and taxonomies ? Simulation and incremental computing ? Information integration ? Security and privacy ? Next-generation applications This event is the culmination of efforts by many talented and dedicated individuals.